PRODUCTION COSTS, PROMOTION, GENERAL ADMINISTRATION, AND SALES VOLUME AGAINST NET PROFIT ON INDUSTRIAL SECTOR COMPANIES LISTED ON IDX - Windy Salsa Febrianti; Heny Triastuti Kurnianingsih; Farida Khairani Lubis (International Journal of Accounting, Finance and Business, 2023)
Interpret processed financial data to see if there is a significant influence between each variable (production costs, promotional costs, general & administrative costs, and sales volume on the company's net profit). The object of this study is financial data for 2019-2021 companies in the consumer goods industry sector listed on the Indonesia Stock Exchange (IDX). The results showed that production costs have a positive influenceon the company's net profit, the calculated t value is greater than the table t, that is, 3. 054 > t-table 1. 99444 with probability Sig. 0.003 < 0.05, promotional costs have a negative influence on the company's net profit because the results of the research test give a t value that is smaller than t table which is 1. 374 < t Table 1. 99444 with probability Sig.0. 174 > 0.05 ,General Expenses &; Administrationistration has a negative influence on the company's net profit The calculated t value is smaller than t table yaitu 0. 505 < t Table 1. 99444 with probability Sig.0. 615>0.05 and sales volume have a positive influence on the company's net profit because the results of the research test produce a calculated t value greater than the table t, which is 6. 944 > t table 1. 99444 with probability Sig.0. 000<0.05.